Social criticism in Oliver Goldsmith’s She Stoops to Conquer (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2022)
Exploring literary work means exploring the social condition of the place where the work created. The function of literary work is not only to amuse but also to criticize. Social criticism implies that many authors convey their view and critics toward their society using literary work. Thus, it is essential to study social criticism in particular literary works. This study is aimed at identifying the social condition of the English society when the work published and to reveal how the author presented the social criticism in his work. Library research was used in this study. The approach that applied was genetic structuralism since any attempt to evaluate a literary work should be in the light of its social context and the proper conditions under which it has been produced. Having analyzed She Stoops to Conquer, it was found that in the eighteen century the English society was to absorbed in vanity and affectation. Most people, especially women, put fashion and physical appearance at the most. The author criticized various aspects of life, including lifestyle, social class and family relationship. The author presented his social criticism through the dialogue and attitude of the characters of the play.